2020
DOI: 10.21203/rs.3.rs-32718/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein convertase subtilisin/Kexin type 9 inhibits hepatocellular carcinoma growth by interacting with GSTP1 and suppressing the JNK signaling pathway

Abstract: Background PCSK9 has been found to be closely related to the occurrence and development of a variety of tumors. However, the concrete role of PCSK9 and its relationship with HCC development is largely unknown. Methods The expression levels of PCSK9 in HCC tissues and HCC cell lines were determined by quantitative real-time polymerase chain reaction (qRT-PCR), western blot and immunohistochemistry assays. The effects of PCSK9 expression on HCC biological traits were investigated by overexpressing and downregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The JNK pathway has been found to interact with multiple GST enzymes, including GSTP1 [ 37 , 38 , 39 ], and these interactions have been shown to promote apoptosis in glioma [ 40 , 41 , 42 ]. We thus hypothesized that the enhancing of drug resistance in GBM by HPGDS may be partially dependent on its inhibition of JNK pathway activation.…”
Section: Resultsmentioning
confidence: 99%
“…The JNK pathway has been found to interact with multiple GST enzymes, including GSTP1 [ 37 , 38 , 39 ], and these interactions have been shown to promote apoptosis in glioma [ 40 , 41 , 42 ]. We thus hypothesized that the enhancing of drug resistance in GBM by HPGDS may be partially dependent on its inhibition of JNK pathway activation.…”
Section: Resultsmentioning
confidence: 99%
“…First, current anti-angiogenic clinical trials induce only a modest improvement in OS, measurable in just several months. Given that HCC has multiple pathways for recruiting vessels, blocking one target alone may have incomplete effects on tumor angiogenesis, because the tumor cells may switch from one mechanism to another 132,138 . However, the use of anti-angiogenic molecules may lead to a hypoxic TME, which alters the cell phenotype and enhances tumor invasiveness, whereas the tumor-infiltrating cells, including TAMs, TANs, and TAFs, may decrease the response to anti-angiogenic therapies 139 .…”
Section: Anti-angiogenic Therapies In Hcc Angiogenesismentioning
confidence: 99%
“…46 On the contrary, other studies reported decreased PCSK9 expression in HCC implying that liver tumors can modulate their local and adjacent microenvironment, thus enabling energy supply to fuel tumor growth. 47 A brilliant study demonstrated that deleting PCSK9 gene in rodent cancer cells substantially affects their growth in vivo and, notably, improves the efficacy of anti-programmed cell death protein 1 (PD1) therapy, opening the way towards combined immune checkpoint-based strategies. Mechanisms of action seem independent of the cholesterol regulation, rather relying on the recycling of MHC I molecules for degradation to lysosomes.…”
Section: Pcsk9 Knockout Micementioning
confidence: 99%